Tradeoffs between inflation and output-gap variances in an optimizing-agent model - Christopher J. Erceg; Dale W. Henderson; Andrew T. Levin (Sveriges Riksbank, 1998)
We demonstrate the existence of a monetary policy tradeoff between price-inflation variability and output-gap variability in an optimizing-agent model with staggered nominal wage and price contracts. This variance tradeoff is absent only in the special case in which prices are sticky and wages are perfectly flexible. When the model is calibrated to exhibit an empirically reasonable degree of nominal wage inertia, strict inflation targeting induces substantial output-gap volatility.
Keywords: 330